Information, sell-side research, and market making☆ - MADUREIRA, L; UNDERWOOD, S (Journal of Financial Economics, 2008)
The interaction between an investment bank's research and market making arms may have important implications for the trading of a firm's stock. We investigate the impact that research has on the liquidity provided by the bank's market maker. Utilizing a large sample of Nasdaq firms, we show that market makers whose banks also provide research coverage provide more liquidity and contribute more to price discovery than do market makers without such research coverage. Finally, we show that such “affiliated” market makers are less affected by uncertainty following earnings announcements. Our results provide new evidence on the sources of liquidity improvements for Nasdaq firms, and suggest that the information produced by banks in the sell-side research process is beneficial to their market makers.